Personal Name and Lineage: Patronym of Arab Descent in Indonesia - Eric Kunto Aribowo (Langkawi: Journal of The Association for Arabic and English, 2020)
Research on patronym recently focuses only on the names of European and Russian communities. The patronyms that appear are limited to the names of the boys who use his father’s name. Arab descent in Indonesia has a more complex patronymic tradition used for male and female, featuring not only the father’s name but also the grandfather’s name as a patron. To fill the gap, this study aimed to explore the forms and patterns of patronyms in the personal names of Arab descent, especially viewed from gender differences by utilizing the onomastic framework. The dataset was taken from the Pasar Kliwon Subdistrict population data which was retrieved from the Population and Civil Registration Agency of Surakarta City. The biological father’s name is juxtaposed to find out and validate the existence of a patronym in the child’s name. The results showed that of 4,756 Arab descent names, 1,114 people (637 males and 477 females) were found who have personal names containing the names of fathers. Only 150 people (92 males and 58 females) have the name of grandfathers in their names. The names of the father and/or grandfather are generally present after the first name and before the surname. Besides being used to claim community membership, patronyms are also intended to show the lineage and the expression of emotional ties between family members. Patronym among Arab descent in Indonesia presents evidence of how the naming system influences robust patrilineal systems and endogamous marriages.